An Enquiry on Fish Selling Culture at South Sumatera: Investigation from Islamic Perspective (Muhammadiyah University Press, 2018)
The diversity in Indonesia makes each region having their model of live, behavior and the mode of transactions. South Sumatera is one of those regions that have been practicing a way of fish sale which is different from others. Fish is sold directly from a pit underneath water flow called lebung through an auction model. This different model of regular sale and auction evokes curiosity as to whether it conforms to shariah requirements or not. The purpose of this research is to investigate the habitual transaction of fish sale in this region. This paper will focus on the practice of people at Seri Kembang I village about the sale by carrying out qualitative approach in a field research involving observation, interview and documentation as the means for collecting data. All data collected will be analyzed through evaluation process by comparing the practice over the actual standard. We conclude that such practice is deemed to be non-permissible since it does not pass some of the standards, especially the garar element. We also provide some suggestion as the alternative of this habitual practice.